A method to assess haul roads rolling resistance using dispatch system data. Issue 3 (3rd July 2021) - Alegre, Douglas; de Lemos Peroni, Rodrigo; da Rosa Aquino, Eduardo; Dille, Felipe
ABSTRACT: Haul roads play a significant role in mining, with rolling resistance being one of the main aspects that can affect road quality and consequently the performance of mining trucks. The aim of this study is to estimate the rolling resistance of haul road segments considering longitudinal grade crossed with dispatch system data using back-calculation from Rimpull curves and estimated performance equations developed by Cooper. The use of this method demonstrated that it could assist in quickly identifying issues on mine haul roads and assess road quality locally through rolling resistance estimated maps, which will help to improve maintenance routines and truck performance.